2011
DOI: 10.1021/ef201378r
|View full text |Cite
|
Sign up to set email alerts
|

Potential for Reduction of Exhaust Emissions in a Common-Rail Direct-Injection Diesel Engine by Fueling with Fischer–Tropsch Diesel Fuel Synthesized from Coal

Abstract: Fischer−Tropsch diesel fuel has desirable physicochemical properties, with the potential to significantly reduce diesel exhaust emissions. This paper evaluates the effects of the use of Fischer−Tropsch diesel fuel synthesized from coal (CFT) on diesel exhaust emissions. A four-cylinder common-rail direct-injection diesel engine fueled with Fischer−Tropsch diesel fuel synthesized from coal, diesel fuel, and blends of the two (15, 30, and 50% CFT by volume) was used. Tests were conducted using the European stati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…F-T diesel is synthesized via the indirect liquefaction of coal using Fischer-Tropsch (F-T) technology [9]. Due to the addition of the coal gasification stage in the production process of F-T diesel, there is a significant difference between coal-to-oil and gas-to-liquid alternatives, including fuel composition, H/C ratio, distillation temperature, and viscosity, all of which play an important role in the formation of exhaust emissions [10]. The price equivalent of F-T diesel from coal is lower than the average crude oil price for the year of study in [11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…F-T diesel is synthesized via the indirect liquefaction of coal using Fischer-Tropsch (F-T) technology [9]. Due to the addition of the coal gasification stage in the production process of F-T diesel, there is a significant difference between coal-to-oil and gas-to-liquid alternatives, including fuel composition, H/C ratio, distillation temperature, and viscosity, all of which play an important role in the formation of exhaust emissions [10]. The price equivalent of F-T diesel from coal is lower than the average crude oil price for the year of study in [11].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, F-T diesel can obtain lower NO x , CO, and soot emissions [5,8,13]. In addition, F-T diesel fuel can be used in conventional diesel engines without any modification, with negligible or minimal engine efficiency gains [10]. F-T diesel can also be blended with other fuels to further improve engine performance.…”
Section: Introductionmentioning
confidence: 99%
“…30 The CO, HC, NO X , and PM emissions present a decreasing trend as the DICL ratio in the fuel is increased. 31…”
Section: Introductionmentioning
confidence: 99%
“…30 The CO, HC, NO X , and PM emissions present a decreasing trend as the DICL ratio in the fuel is increased. 31 As mentioned above, the combustion and emission characteristics of DDCL and DICL has been investigated separately. However, comparative studies on DDCL and DICL is rarely conducted, and the research of DDCL and DICL blends is even less.…”
Section: Introductionmentioning
confidence: 99%
“…Kim et al analyzed the production of Fischer-Tropsch CTL fuel and its potential as an alternative automotive fuel [19]. Song et al discussed the potential of CTL for reducing exhaust emissions in the European steady state cycle (ESC) test mode [20]. The results indicated that the emissions decreased compared with diesel fuel, while there was no obvious difference in the total particle number.…”
Section: Introductionmentioning
confidence: 99%